IMPLEMENTATION NUTRIGENOMIC OF VITAMIN D IN PERIODONTITIS - Hervina, Hervina; Sukrama, I Dewa Made; Jawi, I Made (Journal of Vocational Health Studies, 2022)
Background: Nutrition is a significant risk factor for the incidence of periodontal disease. Nutrients acting on the human genome, either directly or indirectly, can change the expression and structure of genes. One of the micronutrients associated with periodontitis is vitamin D. Vitamin D has an important role in bone and calcium metabolism and regulates serum calcium and phosphate concentrations at normal limits. Purpose: To discuss the nutritional vitamin D as an essential micronutrient in preventing and accelerating healing in periodontitis. Review: Searched two databases from article publication to April 2021, resulting in a total of 66 hits, from which seven relevant articles were selected. VDR signaling can build transcription of genes encoding proactive cytokines, bypassing the cyclo-oxygenase-2 (COX-2) and prostaglandin pathway, and can inhibit matrix metalloproteinase production. The protective mechanism of vitamin D against periodontitis occurs through two biological pathways, namely anti-microbial and anti-inflammatory pathways. The anti-microbial effect of vitamin D results from the binding of 1,25(OH)2D3 with VDR which then induces cAMP, b-def-2 and b-def-3 peptides by macrophages, monocytes, gingival epithelium and periodontal ligament epithelium. The anti-inflammatory effect occurs through decreased production of proinflammatory cytokines. Conclusion: All the signaling effects of VDR can reduce bacteria induced in the inflammatory cytokines so that personalized vitamin D supplementation with an adjusted dose as needed can be used in preventing periodontitis or accelerating the healing of periodontitis.